PENENTUAN SUBCLASSES BERDASARKAN TIPE PESAWAT - Charles AN; Nadya Sartika (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2014)
Based on Break Event Point (BEP) in this article, the most effective plane is Boeing 737-800 used by Sriwijaya Air which has the route from Jakarta to Makassar. The ticket price is ranging. The ticket for the upper class is Rp 1.650.769,- while the lower class is Rp 608.333,- For middle class ticket, the price is Rp 850.000,- The total revenue for a one time flight from Jakarta to Makassar is Rp 211.609.327,-The researcher concludes that Sriwijaya Air with its Boeing 737-800 although offers a reasonable price for the route Jakarta-Makassar still gains high income.